Determinants Of Audit Quality Among Consumer Goods Companies Listed On The Nigerian Stock Exchange - Johnson Kolawole Olowookere; Adesola Olufunmilola Oluwatuyi; Morufu Oladehinde Oladejo (SocioEconomic Challenges)
This study examined the determinants of audit quality among Consumer goods companies listed on the Nigerian stock exchange from 2009 to 2018. This study made use of secondary data obtained from fact books, annual reports, and account of selected consumer goods company under study. The relevant data were subjected to statistical analysis Pearson Correlation while the diagnostics test conducted were Multicollinearity, Autocorrelation, Normality, and Heteroscedasticity Test. The study’s findings showed that board size and company liquidity have a substantial positive influence on financial results, while audit fees, firm size, and audit committee meetings have a negative but non-significant impact. The study concluded that, since board size has a substantial positive effect on audit quality, the governmental body should track firms to ensure that the required board size is met as part of strategies to enhance audit quality among Nigeria’s publicly traded consumer goods companies.